The impact of swimming on the motor activity of children with mental retardation - Grigan S.A. ,; Zakharova N.A. , (Theory and Practice of Physical Culture, 2025)
Physical education and sport is a complex system aimed at solving problems of not only physical but also social development. Small physical activity maintains human health. Today, adaptive sports are becoming a part of the lives of many people with disabilities and changing their lives, both physically and psychologically. The state is actively developing this area of public relations and is making progress in this area. Adaptive sports are becoming a part of the lives of many people with disabilities and changing their lives, both physically and psychologically. Today, adaptive physical education is one of the most important parts in the field of health care and continues to develop rapidly, involving more and more people with disabilities in physical education and sports. Moreover, every year the state is increasingly striving to create the most comfortable conditions for sports for people with health problems. Adaptive physical education not only helps to strengthen, restore and maintain body functions, but also self-realization, develop social aspects of life and integrate into society. The aim of the study is to examine the effect of swimming classes on improving physical, intellectual and emotional indicators in children with mental development problems. According to the results of the study, it can be concluded that swimming classes improve the physical condition of those involved, help keep the body in good shape, despite the difficulties caused by health problems. Moreover, swimming improves coordination, cardiovascular and nervous systems. Classes have a positive psychological effect on this group of people. They do not feel such strong discrimination due to their characteristics and find like-minded people.